Optimalisasi Pengeleloaan Dana Desa untuk Pemberdayaan Ekonomi Berbasis Potensi Lokal: Studi Empiris pada Desa Ranakolo Selatan Kecamatan Maurole Kabupaten Ende Provinsi Nusa Tenggara Timur - Pius Sai; Hyronimus Se; Imaculata Fatima (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Economic empowerment is based on local potential, but optimal implementation still faces challenges and disparities in various regions. This study aims to analyze the management of Village Funds, the determinants of its success, and formulate optimization strategies for economic empowerment based on local potential in South Ranakolo Village. This study uses a qualitative phenomenological approach with a descriptive type. The study location is South Ranakolo Village, Maurole District, Ende Regency, NTT. The main data sources were obtained through in-depth interviews with village officials, the BPD, and community leaders, participatory observation, and documentation. Data analysis follows the Miles and Huberman model: data compression, data presentation, and drawing/verifying conclusions. The results show that the management of Village Funds in South Ranakolo has been based on the principles of Transparency (publication of the Village Budget), Accountability (through the Village Consultative Assembly (MUSDES), Village Work Plan (RKP), and Village Financial Reporting Agency (LKPPD), Participation (MUSDUS and Village Budget Planning (MUSRENBANGDES), and Budgetary Order and Discipline. Economic empowerment efforts are carried out with the principles. Equality (seed assistance, Village-Owned Enterprises), Participation (skills training), Self-Reliance, and Sustainability (utilization of strategic locations). Key factors influencing success are Transparency, Accountability, Community Participation, Village Apparatus Capacity, and Technology/Digital Literacy. Optimization strategies are implemented through a rigorous participatory planning cycle and strengthening the BPD in oversight. Optimization of Village Fund management in South Ranakolo Village is driven by the synergy between transparent and accountable governance, support for active community participation, and strengthening the capacity of village officials and digital literacy. This has a positive impact on improving the village community's independent and sustainable economy.